Effect of electrospinning parameters setting towards fiber diameter - Ngadiman, N.; Noordin, M.; Idris, A.; Kurniawan, Denni (2014)
Fabrication of nanofibers using electrospinning has recently attracted much attention for various applications due to its simplicity. Electrospinning has the ability to produce nanofibers within 100-500 nm. Some applications require certain fiber diameter. As a relatively new process, there are many electrospinning parameters that are believed to influence the nanofiber's diameter. The purpose of this review is to identify and discuss the effect of some of those parameters, i.e. concentration, spinning distance, and applied voltage, and volume flow rate, to the nanofiber diameter during electrospinning process. It was concluded that fiber volume flow rate is proportional to fiber diameter while there is no agreement in reports on other parameters. © (2014) Trans Tech Publications, Switzerland.